The Dynamic Responses of Cell Walls in Resurrection Plants During Dehydration and Rehydration - Chen, Peilei; Jung, Niklas Udo; Giarola, Valentino; Bartels, Dorothea (Frontiers in Plant Science, 2020)
Plant cell walls define the shape of the cells and provide mechanical support. They function as osmoregulators by controlling the transport of molecules between cells and provide transport pathways within the plant. These diverse functions require a well-defined and flexible organization of cell wall components, i.e., water, polysaccharides, proteins, and diverse incrusting substances. Cell walls of desiccation tolerant resurrection plants withstand extreme mechanical stress during complete dehydration and rehydration. Adaptation to the changing water status of the plant plays a crucial role during this process. This review summarizes the compositional and structural variations, signal transduction and changes of gene expression which occur in cell walls of resurrection plants during dehydration and rehydration.